(untitled) (Razi Medical Journal, 2025)
The high increase in diarrhea cases draws the attention of microbiologists to take the necessary precautions against the epidemic that occurs in some regions. It has been found that each year, the mortality and morbidity rates of this infection account for about 500,000 cases in the United States. This retrospective study focuses on the investigation of the rate of C. difficile in a university hospital. Clostridium difficile toxin A / B results of patients admitted to the North Cyprus Near East University hospital between 2015-2018 were retrospectively extracted from the hospital registry system. A total of 230 patient data were used in the study. Data variables used included demographic information, department, and inpatient or outpatient treatment. No significant difference was found in the age category in terms of Clostridium difficile toxin A / B positivity (p = 0.822). The highest positive C. difficile toxin A / B ratio was found in 18.2% in the 20-44 age group, while it was 15.5% in the age group 45 and over. However, there was no statistically significant difference in the age group, as the chi-square result gave a p-value = 0.721. The distribution of this infection showed statistical significance between inpatients and outpatients with a p-value of 0.018. While 9.70% of positivity was detected in inpatients, it was 21.30% in outpatients. The high rate of C. difficile infection among outpatients is due to the unregulated guidelines in the use of antibiotics obtained from pharmaceutical stores. This study shows the inadequacy of rational use of antibiotics in practice, although the sale of antibiotics without a prescription is prohibited in Northern Cyprus.